The Effect of Parenting on Self-Criticism in Adolescents: A Linear Regression Analysis on High School Students - Linda Ernawati; Riana Defianti (Universitas PGRI Yogyakarta, 2025)
Self-criticism is the tendency to judge oneself harshly and negatively, and it commonly appears during adolescence, a key stage in identity development. High levels of self-criticism are linked to mental health issues such as depression, anxiety, self-harm, and suicidal ideation. This study explores how parenting styles influence self-criticism in adolescents. Two hundred sixty-one adolescents aged 15–18 were selected through simple random sampling, with a sample size of 78% female. The study used a parenting style scale (based on Baumrind’s model, adapted by Sianturi et al., 2023) and the Forms of Self-Criticism/Self-Reassuring Scale (FSCRS). Linear regression analysis showed that all four parenting styles, authoritative, authoritarian, permissive, and neglectful, significantly affected self-criticism (p < 0.001). Regression analyses showed authoritarian parenting had the most potent positive effect (β = 0.876, p < 0.001), while authoritative had an adverse impact (β = -0.427, p < 0.001). These findings highlight the importance of parenting in shaping adolescents’ self-evaluation. Future research should consider broader demographics and mediating factors like emotional regulation and social support. Keywords: parenting style, self-criticism, adolescents